Design Of Tourism Destination Information System As A Tourism Service In Nusa Aceh Village - Munawir Munawir; Erdiwansyah Erdiwansyah; Susmanto Susmanto; Zulfan Zulfan (Universitas Serambi Mekkah, 2022)
Desa Wisata Nusa is the only village on the list of the top 50 Indonesian Tourism Village Awards (ADWI) 2021 from the Ministry of Tourism and Creative Economy, which carries the theme of disaster education. The residents of Nusa Village maintain the values of local traditions and culture so that tourists can directly experience the culture in this village. Tourists can stay in traditional wooden stilt houses. The inn was built by the local community independently. With so many opportunities from tourists, it is necessary to have an application that can help this tourist destination so that it can be published to the media, and can also be ordered through the application by tourists. This research aims to develop an application in the form of an android mobile to support integrated tourist destinations by utilizing the potential of the Nusa village and also using the marketplace. This research is development research, where this application was developed using mobile android, the development method in this research is the waterfall form. After doing research, the results are obtained, namely to facilitate the transaction process from tourists so that they can develop the village into a tourist village, because apart from the process of introducing tourist villages, promotions and also seeing potential, the ordering transaction process is also in one application. Keywords: Android Mobile, Tourist village, Geographic Information System, Nusa Village